Social Support and Cardiovascular Risk Factors among Black Adults - Hernandez, Daphne C. (Ethn Dis, 2014)
OBJECTIVE: Cardiovascular disease (CVD) risk factors are prevalent among Black adults. Studies have demonstrated that functional social support buffers CVD risk. The objective of this study is to assess whether specific types of functional social support or their cumulative total buffers CVD risk factors among a convenience sample of Black adults, and whether these associations differ by gender or partner status. DESIGN: Cross-sectional study using self-reported survey data. SETTING: Large church in Houston, TX. PARTICIPANTS: A total of 1,381 Black adults reported their perceived social support using appraisal, belonging, and tangible subscales of the Interpersonal Support Evaluation List-12. A cumulative score was created based on the three subscales. Participants also reported on a number of socio-demographic characteristics. MAIN OUTCOME MEASURES: Three self-reported CVD risk factors: diabetes, high blood pressure, and high cholesterol (yes versus no). RESULTS: A series of multivariate logistic regressions controlling for socio-demographic characteristics were used to calculate adjusted odds ratios (aOR) and 95% confidence intervals (CI) for CVD risk factors. Cumulative social support, rather than any specific type of social support, was significantly related to diabetes and high blood pressure. Higher cumulative social support was associated with lower odds of experiencing diabetes (aOR = 0.97, 95% CI = 0.94, 0.99) and high blood pressure (aOR = 0.98, 95% CI = 0.95, 0.99). Neither gender nor partner status moderated associations. CONCLUSION: In a high risk population for CVD, increasing all types of social support - appraisal, belonging, and tangible - might be useful in preventing or delaying the onset of CVD.